A market decision-making model for load aggregators with flexible load - Wang, Xiaodi; Su, Yunche; Xu, Weiting; Zhang, Shuai; Zhang, Yongjie (Frontiers in Energy Research, 2023)
The fast development of renewable energy has brought great challenges to power system, which urgently need more flexible resources to keep system supply-demand balance. This paper established a multi-stage electricity market framework in the presence of load aggregator (LA), including day-ahead energy/reserve market and real-time balanced market. To actively participate in day-ahead energy market and reserve market, a load profile perception model for LA is proposed to detailly evaluate the response performance of consumers. Meanwhile, a market bidding model of LA and market clearing model of system operator for day-ahead market is also established. To actively join the real-time balance market, a market bidding model of LA for real-time balance market based on surplus flexible resources is established. System operator further clears real-time balance market and dispatch collected flexible resources according to system supply-demand state. A modified IEEE 30 bus system is tested, showing that the proposed market framework can effectively promote consumers to respond to system regulation requirement, and to lower system supply-demand imbalance risk.